Otoproteção da N-acetilcisteína e via de modulação da apoptose em células ciliadas de ratos tratados com cisplatina - Gonçalves, Maiara Santos (2015)
This paper aimed to investigate the apoptosis modulation pathway and the otoprotection mechanism of N-acetylcysteine (NAC) through the analysis of the glutathione peroxidase (GSH-Px) enzyme and the Bcl-2 protein expression in outer hair cells (OHCs) of rats treated with cisplatin. The listening function was also assessed in mice under the effect of different doses of cisplatin and NAC. Two experiments were performed, named A and B, the first being over an experimental period of five days, and the second during three days. Each experiment comprised four groups, under the following protocols: group A1 (negative control): intraperitoneally saline solution 0,9%, in the same volume corresponding to cisplatin dose; group A2 (positive control): 100mg/kg/day of NAC, oral administration by gavage; group A3 (ototoxic): 3mg/kg/day of intraperitoneally cisplatin; group A4 (ototoxic with otoprotection): 100 mg/kg/day of NAC oral administration by gavage, one hour before the administration of 3 mg/kg/day of intraperitoneally cisplatin; group B1 (negative control): intraperitoneally saline solution 0,9% in the same volume corresponding to the cisplatin dose (8mg/kg/day); group B2 (positive control): 300 mg/kg/day of NAC, oral administration by gavage; group B3 (ototoxic): 8 mg/kg/day of intraperitoneally cisplatin; group B4 (ototoxic with otoprotection): 300 mg/kg/day of NAC orally by gavage, one hour before the administration of 8 mg/Kg/day of intraperitoneally cisplatin. The animals in experiment A underwent otoscopy, distortion-product otoacustic emissions (DPOAEs) and brainstem auditory evoked potential (BAEP), before and after the administration of drugs. The animals in experiment B underwent the same testing in pre- and post-treatment, their tympanic bulla being removed ant their cochleae prepared for anatomical assessment with scanning electron microscopy and immunofluorescence for labeling the GSH-Px enzyme and the Bcl-2 protein. In experiment A, it was verified that there was no significant decrease in the signal-to-noise ratio of DPOEAs, but there was a significant increase in the electrophysiologic threshold obtained through BAEP in groups A3 e A4. In experiment B, it was verified that: there was no significant increase in the electrophysiologic threshold obtained through BAEP; the OHCs remained anatomically intact; the GSH-Px enzyme showed immunostaining absent in group B1 and immunostaining present in groups B2, B3 and B4; the Bcl-2 protein showed immunostaining absent in all groups. From the results, it was concluded that the listening function was more impaired by the exposure to a subdose of cisplatin over a longer period, the apoptosis modulation pathway in outer hair cells of mice treated with cisplatin is related to the expression of the GSH-Px enzyme and not expression of the Bcl-2 protein.